EVALUASI KETERLAMBATAN PROYEK PEMBANGUNAN GEDUNG AKIBAT MANAJEMEN DAN PRODUKSI DENGAN METODE EVAS - Desfita, Mediana; Chairi, Maiyozzi; Asraf, Muhammad Bahrul (Ensiklopedia of Journal, 2025)
Delays that occur on a project can delay time and cause cost losses. Delays in construction are said to be the completion of construction within meeting the work time targets exceeding those agreed upon by all parties. This research aims to determine the performance of building project work based on the results of management work delay analysis, evaluate the results of work delay analysis due to production on project work, and find out what factors are obstacles in project work. One method of controlling project costs and time is the evaluation variance at schedule method or what is usually called the EVAS method using the Microsoft Project application. Based on the evaluation results, data obtained on the duration of project work that had been carried out reached the 6th week, to be precise, 42 days, experiencing a setback of 1 day of work, for preliminary work, the duration of work was obtained with a status of 14 days "on schedule", for SMK3 cost work, the duration was 7 days with the status "on schedule", on the lower structure work the work duration was 35 days but experienced a delay of 1 day with the status "management late", on the 1st floor structure work the final duration was 15 days which should have been 14 days with a total slack of 0 days until the status was 'late production".Keywords: Project’s Delays, Buildings Project, Management’s Cause, Production’s Cause, EVAS Methods